2018
DOI: 10.1002/jms.4081
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation‐assisted structural elucidation of compounds containing a tertiary amine side chain using liquid chromatography mass spectrometry

Abstract: A novel analytical technique for the structural elucidation of compounds bearing a tertiary amine side chain via "in vial" instantaneous oxidation and liquid chromatography mass spectrometry (LC-MS) was developed. A series of lidocaine homologs and benzimidazole derivatives with a major/single amine representative base peak in both their EI-MS and ESI-MS/MS spectra were subjected to oxidation by a 0.1% solution of hydrogen peroxide (including several O/ O exchange experiments), followed by LC-ESI-MS/MS analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The main product ions observed were those with an m/z value of 72, 100, and 107, corresponding to either the amine side chain (72 and 100) or the methylethoxybenzene side chain (107). These fragments, as well as the less abundant fragments, match with those obtained for the reference standard and with those proposed for benzimidazole derivatives as found in the literature . Using the LC‐QTOF‐MS method, the compound had a retention time of 5.86 min (the LC‐QTOF chromatogram is shown in Supplementary Data, Figure S2).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The main product ions observed were those with an m/z value of 72, 100, and 107, corresponding to either the amine side chain (72 and 100) or the methylethoxybenzene side chain (107). These fragments, as well as the less abundant fragments, match with those obtained for the reference standard and with those proposed for benzimidazole derivatives as found in the literature . Using the LC‐QTOF‐MS method, the compound had a retention time of 5.86 min (the LC‐QTOF chromatogram is shown in Supplementary Data, Figure S2).…”
Section: Resultssupporting
confidence: 83%
“…These fragments, as well as the less abundant fragments, match with those obtained for the reference standard and with those proposed for benzimidazole derivatives as found in the literature. 31,32 Using the LC-QTOF-MS method, the compound had a retention time of 5.86 min (the LC-QTOF chromatogram is shown in Supplementary Data, Figure S2). Both from the infusion and the chromatographic experiment, a high purity of the compound can be estimated, as no other peaks different from the blank were observed.…”
Section: Lc-qtof-ms Gc-ms and Hplc-dad Analysismentioning
confidence: 99%
“…recently developed. 8 However, for secondary amine analogues, oxidation is ineffective and leads to several byproducts. A more challenging task is to differentiate between positional isomers, which possess an identical exact mass, and to accurately determine their structures because toxicities sometimes vary among isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The observable differences in the fragmentation patterns may have assisted in the distinction between a linear secondary amine derivative and an α-branched amine derivative. For 1 and 3,which are two local anesthetic drugs containing a tertiary amine (lidocaine and bupivacaine), it was recently showed that the oxidation reaction that produces their N-oxide counterparts allows for their structural elucidation by ESI-MS/MS 8.…”
mentioning
confidence: 99%
“…To address the challenge of structural elucidation of compounds bearing a tertiary amine side chain exhibiting information‐poor MS/MS spectra, we have developed several analytical techniques . In this study, we present a new, simple analytical technique based on “in‐vial” chemical derivatization, followed by LC‐ESI‐MS/MS analysis, for the structural elucidation of phenidate analogues which possess a secondary amine residue.…”
Section: Introductionmentioning
confidence: 99%